2015
DOI: 10.1108/jmhtep-06-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Embedding peer support using social work values

Abstract: Purpose -The employment of mental health consumers as peer support workers (PSWs) to provide support to other consumers is gaining momentum around the world. The purpose of this paper is to explore the tensions and dilemmas for a social worker in developing a peer support programme at an inpatient psychiatric service in Australia. The author draws on her experience of embedding a peer support programme providing an insight into the difficulties experienced and strategies used which supported the embedding of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The PCS dimension gave a low forecast with R 2 at 0.349 which implied the employees’ perception of support from co-workers regarding help, encouragement, suggestions, knowledge sharing for learning and development through four questions developed by researchers. The empirical result was consistent with the theory and concept of Beales and Wilson (2015), Blanchard and Thacker (2012), Chiaburu and Harrison (2008), Elias and Upton-Davis (2015), Jenkins et al (2018), Na-nan et al (2017), Qin et al (2018), Thomas and Salzer (2017) and Thompson and Bolino (2018). Furthermore, the four questions were confirmed by statistical analysis and concurred with empirical data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The PCS dimension gave a low forecast with R 2 at 0.349 which implied the employees’ perception of support from co-workers regarding help, encouragement, suggestions, knowledge sharing for learning and development through four questions developed by researchers. The empirical result was consistent with the theory and concept of Beales and Wilson (2015), Blanchard and Thacker (2012), Chiaburu and Harrison (2008), Elias and Upton-Davis (2015), Jenkins et al (2018), Na-nan et al (2017), Qin et al (2018), Thomas and Salzer (2017) and Thompson and Bolino (2018). Furthermore, the four questions were confirmed by statistical analysis and concurred with empirical data.…”
Section: Discussionsupporting
confidence: 87%
“…However, a literature review suggested that not all factors have been tested simultaneously. For example, some researchers studied only factors of PWS, whereas others explored PWS together with PSS (Elias and Upton-Davis, 2015; Jenkins et al , 2018; Qin et al , 2018; Thomas and Salzer, 2017). In addition, some scholars selected to investigate only factors of PCS and PSRS in combination with others.…”
Section: Introductionmentioning
confidence: 99%
“…Social support groups come handy to them. This is because such groups have been known to provide platforms for providing emotional support, information, affirmation, and personal assistance (Cowan, 2018;Chen et al, 2019;Elias & Upton-Davis, 2015;Gowda et al, 2019). Social support is a type of social resource that accumulates through networks of human relationships that protects individuals from the effects of stressors (Robinson & Weiss, 2020).…”
Section: Discussionmentioning
confidence: 99%